Polyurethane anti-needling fabric and preparation method thereof
By applying polyurethane coating on anti-needle fabrics and combining modified nano titanium dioxide and other materials, the existing anti-needle fabrics are solved, and high-performance anti-needle, antibacterial and hydrophobic effects are achieved, satisfying the satisfaction of the high-performance anti-needle fabrics. High-end market demand and simplify production.
Patent Information
- Application Number
- CN202411255615.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
When existing needle-proof fabrics improve their anti-sting performance, they usually lead to reduced thickness, flexibility and comfort of the fabric, and insufficient hydrophobicity, water resistance and antibacterial properties, which cannot meet the needs of the high-end market.
Polyurethane anti-pinning fabric is used to coat the polyurethane coating with a thickness of 120-180 microns on the surface of the base cloth, and combine modified nanotitanium dioxide, modified graphene oxide, modified whiskers and other materials to form high friction and Multifunctional protective layer to improve anti-sting, antibacterial and hydrophobic properties.
It achieves high-performance anti-puncture, antibacterial and hydrophobic properties, maintains the flexibility and comfort of the fabric, extends service life, meets the needs of the high-end market, while simplifying the production process and reducing costs.
Smart Images

Figure BDA0005033957970000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of protective fabrics, and in particular to a polyurethane needle-proof fabric and a preparation method thereof. Background Art
[0002] As people's awareness of protection continues to improve, people's requirements for protective fabrics are also getting higher and higher. In industries that require contact with sharp needles and similar thorny objects, people usually wear gloves or protective clothing for protection during daily work because they will be exposed to thorny objects at work. However, when ordinary fabrics are used, thorny objects will still scratch or penetrate the fabrics, pierce the human body, and cause some damage to people's bodies.
[0003] There are various types of needle-puncture-proof fabrics on the market, which usually improve their needle-puncture-proof performance by increasing the thickness and density of the material. However, these methods often make the fabric thicker and heavier, affecting the wearing comfort and freedom of movement. Existing needle-puncture-proof fabrics mostly use metal wires, ceramic sheets or other hard materials to enhance the anti-puncture performance, but these methods may reduce the flexibility and comfort of the fabric. At the same time, needle-puncture-proof fabrics have poor hydrophobicity, water resistance and antibacterial properties, and cannot meet the needs of the high-end market. Summary of the invention
[0004] The purpose of this application is to provide a polyurethane anti-needle puncture fabric and a preparation method thereof in view of the deficiencies of the current technology. The preparation method of the polyurethane anti-needle puncture fabric of the present application has the advantages of simple preparation and low cost. At the same time, the polyurethane anti-needle puncture fabric has excellent hydrophobicity, antibacterial property, anti-needle puncture, and long service life. The polyurethane anti-needle puncture fabric has high flexibility and comfort, meeting the needs of the high-end market.
[0005] In the first aspect, the present application provides a polyurethane needle-proof fabric, which adopts the following technical solution: A polyurethane needle-proof fabric comprises a base fabric and an needle-proof polyurethane coating arranged on the surface of the base fabric, wherein the thickness of the needle-proof polyurethane coating is 120-180 microns, and the needle-proof polyurethane coating is obtained by coating a polyurethane coating on the surface of the base fabric and curing the coating. The material of the base fabric is at least one of a chemical fiber material, a natural fiber material, and a mineral fiber material. The needle-proof polyurethane coating or a polyurethane coating formed by adding glass fiber, quartz, and silicon carbide microparticles can effectively increase friction, thereby improving the needle-proof performance of the needle-proof fabric. The polyurethane coating, in parts by mass, comprises the following preparation raw materials: 85-90 parts of a modified polyurethane emulsion, 20-25 parts of a modified graphene oxide dispersion, 8-10 parts of modified whisker blended carbon fiber, and 5-7 parts of modified nano titanium dioxide. The needle-proof polyurethane coating or a polyurethane coating formed by adding glass fiber, quartz, and silicon carbide microparticles can effectively increase friction, thereby improving the needle-proof performance of the needle-proof fabric.
[0006] By adopting the above technical solutions, base fabric: As the basic structure of the fabric, the base fabric provides the necessary physical strength and durability. Selecting materials with good flexibility and durability such as chemical fiber materials, natural fiber materials, mineral fiber materials, etc. can ensure the durability of the fabric in daily use. The base fabric also provides an adhesion surface for the upper polyurethane coating, and its structure has a direct impact on the uniformity and adhesion strength of the coating. Anti-needle puncture polyurethane coating: This coating is the core part of this fabric and is formed by coating on the surface of the base fabric and curing. Its thickness is controlled at 120-180 microns to ensure sufficient protection without excessively increasing weight or affecting flexibility. The coating not only provides physical protection to prevent the penetration of spiked objects, but also has hydrophobic and antibacterial properties due to its unique chemical composition. Modified polyurethane emulsion: As the main component of the coating, the modified polyurethane emulsion effectively improves the water resistance of the fabric and prevents water penetration by introducing hydrophobic di-terminal hydroxybutyl polydimethylsilane. The modification process enhances the compatibility between the polyurethane chain and the polyacrylate chain, reduces phase separation, and thus improves the water resistance and flexibility of the coating. Modified nano-titanium dioxide: The addition of modified nano-titanium dioxide improves its dispersibility and compatibility in the coating, which helps to form a more uniform coating and avoid agglomeration. Nano-titanium dioxide itself has antibacterial properties, and after modification, it can better combine with polyurethane, further improving the antibacterial and anti-puncture properties of the fabric. Modified whisker-blended carbon fibers: The dispersibility and compatibility of these fibers in the coating have also been improved, and their addition significantly enhances the anti-puncture ability of the fabric. Whisker-blended carbon fibers can effectively block or slow down the penetration of sharp objects due to their own high strength and stiffness. Modified graphene oxide dispersion: Through specific modifiers, the interaction between graphene oxide and polyurethane is enhanced, which not only improves the dispersion concentration but also improves the stability of the coating. The addition of modified graphene oxide, using its unique two-dimensional structural characteristics, further enhances the antibacterial and anti-puncture properties of the fabric. In summary, the role of each layer of material in this application is to form a high-performance fabric with excellent hydrophobicity, antibacterial and anti-needle puncture properties through their own unique properties and synergistic effects. This fabric can not only provide effective physical protection, but also provide additional functionality such as antibacterial and hydrophobicity through its chemical properties to meet the needs of the high-end market.
[0007] Preferably, the preparation method of the modified nano titanium dioxide is as follows: 300 parts of nano titanium dioxide with a particle size of 20 nanometers, 7 parts of concentrated sulfuric acid with a mass concentration of 98%, 75 parts of xylene, and 15 parts of 1,6-dipic acid are added to a three-necked flask with a stirring device and a thermometer according to the mass parts, the temperature is raised to 132° C., and the temperature is kept until the acid value is less than 0.1 mgKOH / g, triethylamine is added to neutralize to a pH of 7.5, and the solvent is removed by negative pressure distillation to obtain modified nano titanium dioxide.
[0008] By adopting the above technical scheme, the preparation method of modified nano titanium dioxide involves multiple steps, aiming to improve its dispersibility and compatibility in polyurethane coatings, thereby enhancing the antibacterial and anti-needle puncture properties of fabrics. First, 300 parts of nano titanium dioxide with a particle size of 20 nanometers are added to a three-necked flask with a stirring device and a thermometer. Such nanoparticles have a high specific surface area due to their small size, which enhances their reactivity. Then, 7 parts of concentrated sulfuric acid with a mass concentration of 98% and 75 parts of xylene and 15 parts of 1,6-hexanedioic acid are added. The addition of concentrated sulfuric acid helps to introduce sulfate groups on the surface of nano titanium dioxide and increase its hydrophilicity, while xylene and 1,6-hexanedioic acid serve as solvents and additives to help control the reaction conditions and improve the surface properties of nanoparticles. The mixture is heated to 132°C and kept warm until the acid value is less than 0.1 mgKOH / g. This step is to promote chemical reactions by heating to make the surface modification of nano titanium dioxide more complete. After the reaction is completed, triethylamine is added to neutralize to a pH of 7.5, and an alkaline substance is used to neutralize the excess acid and adjust the pH to neutral to meet the needs of subsequent applications. The solvent is then removed by negative pressure distillation to obtain pure modified nano titanium dioxide. The dispersibility of the modified nano titanium dioxide in polyurethane coatings is significantly improved. This is because its surface is chemically modified to increase its compatibility with polyurethane and reduce the agglomeration between particles. Nano titanium dioxide itself has certain antibacterial properties, and these properties are further exerted after modification. In fabrics, this provides an additional layer of health protection and reduces bacterial growth. The addition of modified nano titanium dioxide enhances the overall strength and durability of the fabric, especially in resisting penetration by sharp objects, and improves the fabric's anti-needle puncture ability. Modified nano titanium dioxide works together with other ingredients such as modified polyurethane emulsion, modified graphene oxide dispersion, and modified whisker blended carbon fiber to form a multifunctional protective layer. The synergistic effect of these ingredients not only improves the physical protection properties of the fabric, but also enhances its chemical stability and durability. In summary, modified nano-titanium dioxide not only improves its dispersibility and compatibility in polyurethane coatings through specific chemical treatment, but also provides comprehensive performance improvement for fabrics together with other ingredients through its inherent antibacterial properties and enhanced anti-needle puncture ability.
[0009] Preferably, the method for preparing the modified whisker blended carbon fiber comprises the following steps: S41, according to the mass fraction, 100 parts of aluminum borate whiskers with a diameter of 1-5 μm and an aspect ratio of 10-15 are sent to 300 parts of 95% concentrated sulfuric acid for treatment for 40-60 minutes, and then washed with boiling water for 3 times and dried to obtain hydroxylated aluminum borate whiskers; S42. Add 100 parts of hydroxylated aluminum borate whiskers, 50 parts of carbon fibers with a diameter of 10-15 μm and an aspect ratio of 10-15, and 6 parts of silane coupling agents to 12 parts of an ethanol solution of sodium dithiopropane sulfonate with a mass concentration of 15%, stir thoroughly, and obtain modified whisker-blended carbon fibers.
[0010] By adopting the above technical scheme, the preparation method of modified whisker blended carbon fiber involves two main steps: the preparation of hydroxylated aluminum borate whiskers and the modification and blending of carbon fiber. These steps are intended to improve the surface activity of carbon fiber and aluminum borate whiskers, promote their dispersibility and compatibility in polyurethane coatings, and thus enhance the anti-needle puncture performance of fabrics. Preparation of hydroxylated aluminum borate whiskers (S41): 100 parts of aluminum borate whiskers with a diameter of 1-5 μm and an aspect ratio of 10-15 are added to 300 parts of concentrated sulfuric acid with a mass concentration of 95% and treated for 40-60 minutes. This step uses strong acid treatment to introduce hydroxyl groups on the surface of aluminum borate whiskers to increase their surface activity and hydrophilicity. After treatment, the whiskers are washed three times with boiling water to remove excess sulfuric acid, and then dried to obtain hydroxylated aluminum borate whiskers. Preparation of modified whisker blended carbon fiber (S42): 100 parts of hydroxylated aluminum borate whiskers, 50 parts of carbon fibers with a diameter of 10-15 μm and an aspect ratio of 10-15 and 6 parts of silane coupling agents are added to 12 parts of an ethanol solution of sodium dithiopropane sulfonate with a mass concentration of 15%, and stirred thoroughly. In this step, the silane coupling agent acts as a bridge to help the hydroxylated aluminum borate whiskers combine with the carbon fibers, while the ethanol solution of sodium dithiopropane sulfonate provides a suitable reaction medium, which promotes the chemical modification. Through the treatment of hydroxylation and silane coupling agents, the dispersibility and compatibility of modified whisker blended carbon fibers in polyurethane coatings are significantly improved. This helps the carbon fibers and aluminum borate whiskers to be more evenly distributed in the coating, reducing agglomeration, thereby forming a more uniform and tight protective layer. The addition of modified whisker blended carbon fibers significantly improves the needle puncture resistance of the fabric due to the high strength and rigidity of the carbon fibers themselves, as well as the hardness and stability of the aluminum borate whiskers. The network structure formed by these fibers and whiskers in the fabric can effectively block or slow down the penetration of sharp objects. The modified whisker blended carbon fiber works together with other ingredients such as modified polyurethane emulsion, modified graphene oxide dispersion and modified nano-titanium dioxide to form a multifunctional protective layer. The synergistic effect of these ingredients not only improves the physical protective properties of the fabric, but also enhances its chemical stability and durability. In summary, the modified whisker blended carbon fiber has not only improved its dispersibility and compatibility in polyurethane coatings through specific chemical treatment, but also provides comprehensive performance improvements for fabrics through its inherent physical properties and enhanced anti-needle puncture ability together with other ingredients.
[0011] Preferably, the silane coupling agent is composed of isopropyl trioleyl titanate, γ-aminopropyl triethoxysilane and tri(dodecylbenzenesulfonyl) titanate isopropyl in a mass ratio of 3:4:3.
[0012] By adopting the above technical solutions, isopropyl trioleyl titanate: As a titanate coupling agent, it can react with the hydroxyl groups on the surface of aluminum borate whiskers and carbon fibers to form stable chemical bonds. This helps to improve the adhesion between the fiber and the polyurethane and enhance the overall performance of the coating. γ-aminopropyl triethoxysilane: This silane coupling agent reacts with the hydroxyl groups on the fiber surface through its ethoxy group, and its aminopropyl part can react with the isocyanate group in the polyurethane to form a bridge between the fiber and the polymer matrix. Tri(dodecylbenzenesulfonyl) isopropyl titanate: This titanate coupling agent has a long alkyl chain and a benzenesulfonyl group, which can provide additional hydrophobicity and enhance the dispersibility of the fiber in an aqueous medium. Isopropyl trioleyl titanate and γ-aminopropyl triethoxy silane work together to greatly enhance the adhesion of the interface by forming chemical bonds with the fiber surface and the polyurethane matrix. This helps to improve the mechanical strength and durability of the coating. The hydrophobic long chain and benzenesulfonyl group of tri(dodecylbenzenesulfonyl)titanate isopropyl provide good dispersibility in aqueous media, while γ-aminopropyltriethoxysilane ensures that this dispersibility is maintained after the coating is cured through chemical reaction. The synergistic effect of these three coupling agents not only improves the dispersibility and compatibility of the fiber in the coating, but also enhances the hydrophobicity, antibacterial and anti-needle puncture properties of the coating by enhancing the interaction between the fiber and the polymer matrix. In summary, the reasonable ratio and synergistic effect of silane coupling agents are crucial to the performance of modified whisker-blended carbon fibers. Together, they provide a versatile platform that significantly improves the overall performance of polyurethane anti-needle puncture fabrics through the formation of chemical bonds and the enhancement of physical effects, meeting the needs of the high-end market.
[0013] Preferably, the method for preparing the modified graphene oxide dispersion comprises the following steps: S61. According to the mass fraction, 10 parts of graphene oxide are added to 50 parts of N,N-dimethylformamide aqueous solution with a mass concentration of 5%, and stirred evenly. 0.3 parts of thionyl chloride are added at 0-4°C. After the addition is completed, the reaction is carried out for 3 hours, and the temperature is raised to 50°C. During the process, condensation and reflux are carried out and tail gas absorption is carried out at the same time. After the reaction is carried out for 6-8 hours, an appropriate amount of deionized water is slowly added until no gas is generated in the system, and then suction filtration and washing are carried out to obtain modified graphene oxide; S62. Re-disperse 10 parts of modified graphene oxide in 100 parts of water, disperse under high-speed stirring for 40 minutes, and then shear emulsify and homogenize for 4 hours to obtain a uniform dispersion, then add sodium 2-[(2-aminoethyl)amino]ethanesulfonate, react at 60°C for 8 hours to obtain a modified graphene oxide dispersion.
[0014] By adopting the above technical scheme, the preparation method of modified graphene oxide dispersion involves two main steps: first, modifying the graphene oxide through a chemical reaction; second, re-dispersing and stabilizing the modified graphene oxide to obtain a dispersion suitable for use in polyurethane coatings.
[0015] Add 10 parts of graphene oxide to 50 parts of N,N-dimethylformamide aqueous solution with a mass concentration of 5% and stir evenly. This step is to fully disperse the graphene oxide in the solvent for the subsequent chemical reaction. Add 0.3 parts of thionyl chloride at 0-4°C, and react for 3 hours after the addition is completed. As a modifier, thionyl chloride reacts with the hydroxyl and carboxyl groups on the graphene oxide under this condition to introduce new functional groups. Raise the temperature to 50°C, condense and reflux during the reaction, and absorb the tail gas at the same time. After 6-8 hours of reaction, slowly add an appropriate amount of deionized water until no gas is generated in the system. This step promotes the completion of the chemical reaction by heating, and stops the reaction by adding deionized water. Finally, filter and wash to obtain modified graphene oxide. These washing steps ensure that unreacted chemicals are removed, leaving pure modified graphene oxide. 10 parts of modified graphene oxide were redispersed in 100 parts of water, dispersed under high-speed stirring for 40 minutes, and then sheared and emulsified for 4 hours to obtain a uniform dispersion. These steps ensured the uniform dispersion of modified graphene oxide in water and formed a stable colloidal system. Subsequently, sodium 2-[(2-aminoethyl)amino]ethanesulfonate was added and reacted at 60°C for 8 hours to obtain a modified graphene oxide dispersion. This step further stabilizes the dispersion by adding specific compounds to prevent particle aggregation and sedimentation. The dispersibility of modified graphene oxide in polyurethane coatings is significantly improved through the above preparation process. This ensures that graphene oxide can be evenly distributed in the coating, thereby more effectively enhancing the performance of the coating. The modified graphene oxide and polyurethane segments chemically act on graphene oxide to form a polyurethane coating that can be stable for a long time. This strong interaction helps to improve the mechanical strength and durability of the coating. The introduction of modified graphene oxide enhances the antibacterial and anti-needle puncture properties of the fabric by utilizing its unique two-dimensional structural characteristics. Especially when combined with other ingredients such as modified polyurethane emulsion, modified whisker blended carbon fiber and modified nano-titanium dioxide, a multifunctional protective layer is formed, which improves the overall performance of the fabric. In summary, the preparation of modified graphene oxide dispersion not only improves its dispersibility and compatibility in polyurethane coatings, but also provides comprehensive performance improvements for fabrics through its inherent properties and synergistic effects with other ingredients, especially in terms of antibacterial and anti-needle puncture capabilities.
[0016] Preferably, the mass ratio of the modified graphene oxide to the sodium 2-[(2-aminoethyl)amino]ethanesulfonate is 1:3-4.
[0017] Preferably, the preparation method of the modified polyurethane emulsion comprises the following steps: S81. Mix 71 parts of di-terminal hydroxybutyl polydimethylsilane, 114 parts of butyl acrylate, 61 parts of styrene, 89 parts of polycaprolactone, 33 parts of isophorone diisocyanate, 3 parts of hydroxyethyl methacrylate, 1.8 parts of azobisisobutyronitrile, 0.5 parts of dibutyltin dilaurate and 10.5 parts of n-hexadecane in parts by mass to obtain a mixture; S82. Add the mixture into 300 parts of an aqueous emulsifier solution with a mass concentration of 5%, and then pre-emulsify at 2000r / min to obtain a crude emulsion, and then use a cell crusher to ultrasonically treat it in an ice-water bath for 30 minutes to obtain a monomer fine emulsion. Finally, stir the obtained monomer fine emulsion in a nitrogen atmosphere for 1 hour, transfer it to a three-necked flask, maintain the temperature at 70°C and carry out a fine emulsion polymerization reaction in a nitrogen environment for 6 hours to obtain a modified polyurethane emulsion.
[0018] By adopting the above technical scheme, the modified polyurethane emulsion successfully introduced dihydroxybutyl polydimethylsilane into the polyurethane chain segment through the miniemulsion polymerization method to obtain a modified polyurethane emulsion. The addition of dihydroxybutyl polydimethylsilane improves the compatibility between the polyurethane chain and the polyacrylate chain and reduces the degree of phase separation. The introduction of hydrophobic dihydroxybutyl polydimethylsilane can inhibit water molecules from penetrating from the surface of the polyurethane anti-needle puncture fabric to the interior of the fabric, thereby improving the water resistance and flexibility of the anti-needle puncture polyurethane coating.
[0019] Preferably, the emulsifier is 1-allyloxy-3-4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate.
[0020] In the second aspect, the present application provides a method for preparing a polyurethane anti-needle puncture fabric, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned polyurethane anti-needle puncture fabric, comprising the following steps: S101, uniformly stirring the modified polyurethane emulsion, the modified graphene oxide dispersion, the modified whisker-blended carbon fiber and the modified nano-titanium dioxide according to their weight fractions to obtain a polyurethane coating; S102, coating the polyurethane coating on the surface of the base fabric, ensuring that the polyurethane coating can completely cover the base fabric and penetrate into the fibers thereof; S103, pressing the base fabric coated with the polyurethane coating so that the gaps in the base fabric are completely filled with the polyurethane coating, and then drying at 80-85°C for 30-40 minutes to obtain the polyurethane anti-needle puncture fabric.
[0021] In summary, the beneficial technical effects of this application are: 1. Enhanced physical protection: By applying a 120-180 micron thick polyurethane coating on the base fabric and combining it with modified whiskers to mix carbon fibers, the fabric can effectively prevent the penetration of sharp objects and provide excellent anti-needle puncture protection. This is especially important for work clothing or outdoor sports equipment that require high safety protection.
[0022] 2. Excellent waterproof and antibacterial properties: The introduction of modified polyurethane emulsion, especially the addition of hydrophobic di-terminal hydroxybutyl polydimethylsilane, significantly improves the water resistance of the fabric, enabling the fabric to resist water penetration while maintaining breathability. In addition, the addition of modified nano-titanium dioxide improves the antibacterial properties of the fabric, reduces the possibility of bacterial growth, and thus increases the hygienic safety of the fabric.
[0023] 3. Improved durability and comfort: Mini-emulsion polymerization improves the compatibility between polyurethane chains and polyacrylate chains, reduces the degree of phase separation, and not only improves the water resistance of the coating, but also enhances its flexibility. The combination of these characteristics ensures that the fabric maintains its performance during long-term use while providing good comfort, meeting the high-end market's demand for high quality, durability and comfortable wearing.
[0024] 4. Environmentally friendly materials: The polyurethane coating used is more environmentally friendly than traditional oil-based polyurethane, reduces the use of harmful solvents, and meets the requirements of modern sustainable development.
[0025] 5. Simplified production process and cost-effectiveness: The preparation method is designed with the need to simplify the production process and reduce costs in mind, allowing this high-performance fabric to be mass-produced in a relatively economical manner to meet a wide range of market demands. DETAILED DESCRIPTION
[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] Preparation Example 1 Modified Nano Titanium Dioxide The preparation method of modified nano titanium dioxide is as follows: according to the mass fractions, 300g of nano titanium dioxide with a particle size of 20 nanometers, 7g of concentrated sulfuric acid with a mass concentration of 98%, 75g of xylene, and 15g of 1,6-dipic acid are added into a three-necked flask with a stirring device and a thermometer, the temperature is raised to 132°C, and the temperature is kept until the acid value is less than 0.1mgKOH / g, triethylamine is added to neutralize to a pH of 7.5, and the solvent is removed by negative pressure distillation to obtain modified nano titanium dioxide.
[0028] Preparation Example 2 Preparation of modified polyurethane emulsion The preparation method of modified polyurethane emulsion comprises the following steps: S81. According to the mass fractions, 71 g of di-terminal hydroxybutyl polydimethylsilane, 114 g of butyl acrylate, 61 g of styrene, 89 g of polycaprolactone, 33 g of isophorone diisocyanate, 3 g of hydroxyethyl methacrylate, 1.8 g of azobisisobutyronitrile, 0.5 g of dibutyltin dilaurate and 10.5 g of n-hexadecane were mixed uniformly to obtain a mixture; S82. Add the mixture into 300 g of 5% mass concentration of 1-allyloxy-3-4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate aqueous solution, then pre-emulsify at 2000 r / min to obtain a crude emulsion, and then use a cell crusher to ultrasonically treat it in an ice water bath for 30 minutes to obtain a monomer fine emulsion. Finally, stir the obtained monomer fine emulsion in a nitrogen atmosphere for 1 hour, transfer it to a three-necked flask, maintain the temperature at 70°C and carry out a fine emulsion polymerization reaction in a nitrogen environment for 6 hours to obtain a modified polyurethane emulsion.
[0029] Preparation Example 3 Preparation of modified graphene oxide dispersion The preparation method of modified graphene oxide dispersion comprises the following steps: S61. According to the mass fraction, 10 g of graphene oxide was added to 50 g of an aqueous solution of N,N-dimethylformamide with a mass concentration of 5%, and stirred evenly. 0.3 g of thionyl chloride was added at 3°C. After the addition was completed, the mixture was reacted for 3 hours, and the temperature was raised to 50°C. During the reaction, the mixture was condensed and refluxed, and tail gas was absorbed at the same time. After the reaction was carried out for 7 hours, an appropriate amount of deionized water was slowly added until no gas was generated in the system, and the mixture was filtered and washed to obtain modified graphene oxide. S62. Re-disperse 10 g of modified graphene oxide in 100 g of water, disperse under high-speed stirring for 40 minutes, and then shear emulsify and homogenize for 4 hours to obtain a uniform dispersion, then add 35 g of sodium 2-[(2-aminoethyl)amino]ethanesulfonate, react at 60°C for 8 hours to obtain a modified graphene oxide dispersion.
[0030] Preparation Example 4 Preparation of modified whisker blended carbon fiber The method for preparing modified whisker blended carbon fiber comprises the following steps: S41. According to the mass fractions, 100 g of aluminum borate whiskers with a diameter of 1-5 μm and an aspect ratio of 10-15 are sent to 300 g of concentrated sulfuric acid with a mass concentration of 95% for treatment for 50 minutes, and then washed with boiling water for 3 times and dried to obtain hydroxylated aluminum borate whiskers; S42. 100 g of hydroxylated aluminum borate whiskers, 50 g of carbon fibers with a diameter of 10-15 μm and an aspect ratio of 10-15 and 6 g of a silane coupling agent are added to 12 g of an ethanol solution of sodium dithiopropane sulfonate with a mass concentration of 15%, and stirred sufficiently to obtain modified whisker-blended carbon fibers, wherein the silane coupling agent is composed of isopropyl trioleyl titanate, γ-aminopropyl triethoxysilicon and isopropyl tri(dodecylbenzenesulfonyl) titanate in a mass ratio of 3:4:3.
[0031] Preparation Example Comparative Example 1 The same as Preparation Example 4, except that: the silane coupling agent is isopropyl trioleate acyloxy titanate.
[0032] Preparation Example Comparative Example 2 The same as Preparation Example 4, except that the silane coupling agent is γ-aminopropyltriethoxysilane.
[0033] Preparation Example Comparative Example 3 The same as Preparation Example 4, except that the silane coupling agent is tri(dodecylbenzenesulfonyl)titanate isopropyl ester.
[0034] Preparation Example Comparative Example 4 Preparation of polyurethane emulsion The preparation method of polyurethane emulsion comprises the following steps: S81. According to the mass fractions, 114 g of butyl acrylate, 61 g of styrene, 89 g of polycaprolactone, 33 g of isophorone diisocyanate, 3 g of hydroxyethyl methacrylate, 1.8 g of azobisisobutyronitrile, 0.5 g of dibutyltin dilaurate and 10.5 g of n-hexadecane were mixed uniformly to obtain a mixture; S82. Add the mixture into 300 g of 5% mass concentration of 1-allyloxy-3-4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate aqueous solution, then pre-emulsify at 2000 r / min to obtain a crude emulsion, and then use a cell crusher to ultrasonically treat it in an ice water bath for 30 minutes to obtain a monomer fine emulsion. Finally, stir the obtained monomer fine emulsion in a nitrogen atmosphere for 1 hour, transfer it to a three-necked flask, maintain the temperature at 70°C and carry out a fine emulsion polymerization reaction in a nitrogen environment for 6 hours to obtain a modified polyurethane emulsion.
[0035] Example 1 A polyurethane needle-proof fabric comprises a chemical fiber material base fabric and an needle-proof polyurethane coating arranged on the surface of the chemical fiber material base fabric, wherein the thickness of the needle-proof polyurethane coating is 120 microns, and the needle-proof polyurethane coating is prepared by coating a polyurethane coating on the surface of the base fabric and curing it, wherein the polyurethane coating comprises the following preparation raw materials in parts by mass: 850g of modified polyurethane emulsion, 200g of modified graphene oxide dispersion, 80g of modified whisker-blended carbon fiber, and 50g of modified nano titanium dioxide, and the modified whisker-blended carbon fiber is prepared as in Preparation Example 4.
[0036] The method for preparing the above-mentioned polyurethane needle-proof fabric comprises the following steps: S101, uniformly stirring the modified polyurethane emulsion, the modified graphene oxide dispersion, the modified whisker-blended carbon fiber and the modified nano-titanium dioxide according to their weight fractions to obtain a polyurethane coating; S102, applying the polyurethane coating on the surface of the chemical fiber base fabric, ensuring that the polyurethane coating can completely cover the base fabric and penetrate into the fibers thereof; S103, pressing the chemical fiber base fabric coated with the polyurethane coating to completely fill the gaps in the chemical fiber base fabric with the polyurethane coating, and then drying at 80° C. for 40 minutes to obtain the polyurethane anti-needle puncture fabric.
[0037] Example 2 A polyurethane needle-proof fabric comprises a natural fiber material base fabric and an needle-proof polyurethane coating arranged on the surface of the natural fiber material base fabric, wherein the thickness of the needle-proof polyurethane coating is 180 microns, and the needle-proof polyurethane coating is prepared by coating a polyurethane coating on the surface of the base fabric and curing it, wherein the polyurethane coating comprises the following preparation raw materials in parts by mass: 900 g of modified polyurethane emulsion, 250 g of modified graphene oxide dispersion, 100 g of modified whisker-blended carbon fiber, and 70 g of modified nano titanium dioxide, and the modified whisker-blended carbon fiber is prepared as in Preparation Example 4.
[0038] The method for preparing the above-mentioned polyurethane needle-proof fabric comprises the following steps: S101, uniformly stirring the modified polyurethane emulsion, the modified graphene oxide dispersion, the modified whisker-blended carbon fiber and the modified nano-titanium dioxide according to their weight fractions to obtain a polyurethane coating; S102, applying the polyurethane coating on the surface of the natural fiber base fabric, ensuring that the polyurethane coating can completely cover the base fabric and penetrate into the fibers thereof; S103, pressing the natural fiber base fabric coated with the polyurethane coating to completely fill the gaps in the natural fiber base fabric with the polyurethane coating, and then drying at 85° C. for 30 minutes to obtain the polyurethane anti-needle puncture fabric.
[0039] Example 3 A polyurethane needle-proof fabric comprises a mineral fiber material base fabric and a needle-proof polyurethane coating arranged on the surface of the mineral fiber material base fabric, wherein the thickness of the needle-proof polyurethane coating is 150 microns, and the needle-proof polyurethane coating is prepared by coating a polyurethane coating on the surface of the base fabric and curing it, wherein the polyurethane coating comprises the following preparation raw materials in parts by mass: 870g of modified polyurethane emulsion, 230g of modified graphene oxide dispersion, 90g of modified whisker-blended carbon fiber, and 60g of modified nano titanium dioxide, and the modified whisker-blended carbon fiber is prepared as in Preparation Example 4.
[0040] The method for preparing the above-mentioned polyurethane needle-proof fabric comprises the following steps: S101, uniformly stirring the modified polyurethane emulsion, the modified graphene oxide dispersion, the modified whisker-blended carbon fiber and the modified nano-titanium dioxide according to their weight fractions to obtain a polyurethane coating; S102, applying the polyurethane coating on the surface of the mineral fiber base fabric, ensuring that the polyurethane coating can completely cover the base fabric and penetrate into the fibers thereof; S103, pressing the mineral fiber base fabric coated with the polyurethane coating to completely fill the gaps in the mineral fiber base fabric with the polyurethane coating, and then drying at 83° C. for 35 minutes to obtain the polyurethane anti-needle puncture fabric.
[0041] Comparative Example 1 The same as Example 3, except that the modified whisker blended carbon fiber is prepared according to Comparative Example 1.
[0042] Comparative Example 2 The same as Example 3, except that the modified whisker blended carbon fiber is prepared according to Comparative Example 2.
[0043] Comparative Example 3 The same as Example 3, except that the modified whisker blended carbon fiber is prepared according to Preparation Comparative Example 3.
[0044] Comparative Example 4 The same as Example 3, except that nano titanium dioxide with an equal particle size of 20 nanometers is used instead of the modified nano titanium dioxide.
[0045] Comparative Example 5 The same as Example 3, except that an equal amount of the polyurethane emulsion prepared in Preparation Example Comparative Example 4 is used instead of the modified polyurethane emulsion.
[0046] Performance Testing The polyurethane needle-proof fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were sampled and subjected to the following tests. The test results are shown in Table 1.
[0047] Needle puncture test: According to ASTM F2878-2010, standard test method for the resistance of protective clothing materials to injection needle puncture; use a 25G hypodermic needle for testing; Water resistance is expressed by water contact angle; the water contact angle is measured by a video contact angle meter; The detection method of the inhibition rate refers to the oscillation method in the GB / T20944.3-2008 standard for antibacterial experiments.
[0048] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The polyurethane anti-needle puncture fabrics prepared in Examples 1 to 3 have excellent hydrophobicity, antibacterial properties, anti-needle puncture properties, and long service life. The polyurethane anti-needle puncture fabrics are highly flexible and comfortable, meeting the needs of the high-end market.
[0049] 2) The comparative analysis of the performance of the polyurethane anti-needle puncture fabrics prepared in Example 3 and Comparative Examples 1 to 3 shows that the silane coupling agent is composed of isopropyl trioleyl titanate, γ-aminopropyl triethoxysilane and tri(dodecylbenzenesulfonyl) titanate isopropyl ester in a mass ratio of 3:4:3. The synergistic effect of these three coupling agents not only improves the dispersibility and compatibility of the fiber in the coating, but also enhances the interaction between the fiber and the polymer matrix, thereby improving the hydrophobicity, antibacterial and anti-needle puncture properties of the coating.
[0050] 3) The performance comparison analysis of the polyurethane anti-needle puncture fabric prepared in combination with Example 3 and Comparative Example 4 shows that the dispersibility of modified nano titanium dioxide in polyurethane coating is significantly improved. This is because its surface is chemically modified, which increases the compatibility with polyurethane and reduces the agglomeration between particles. Nano titanium dioxide itself has certain antibacterial properties, and these properties are further exerted after modification. In the fabric, this provides an additional health protection layer and reduces the growth of bacteria. The addition of modified nano titanium dioxide enhances the overall strength and durability of the fabric, especially in resisting penetration by sharp objects, and improves the fabric's anti-needle puncture ability. Modified nano titanium dioxide works together with other ingredients such as modified polyurethane emulsion, modified graphene oxide dispersion, and modified whisker blended carbon fiber to form a multifunctional protective layer. The synergistic effect of these ingredients not only improves the physical protection properties of the fabric, but also enhances its chemical stability and durability. In summary, modified nano-titanium dioxide not only improves its dispersibility and compatibility in polyurethane coatings through specific chemical treatment, but also provides comprehensive performance improvement for fabrics together with other ingredients through its inherent antibacterial properties and enhanced anti-needle puncture ability.
[0051] 4) The performance comparison analysis of the polyurethane anti-needle puncture fabrics prepared in combination with Example 3 and Comparative Example 5 shows that the modified polyurethane emulsion successfully introduces dihydroxybutyl polydimethylsilane into the polyurethane chain segment by miniemulsion polymerization to obtain a modified polyurethane emulsion. The addition of dihydroxybutyl polydimethylsilane improves the compatibility between the polyurethane chain and the polyacrylate chain and reduces the degree of phase separation. The introduction of hydrophobic dihydroxybutyl polydimethylsilane can inhibit water molecules from penetrating from the surface of the polyurethane anti-needle puncture fabric to the interior of the fabric, thereby improving the water resistance and flexibility of the anti-needle puncture polyurethane coating.
[0052] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A polyurethane needle-proof fabric, characterized in that: The invention comprises a base fabric and a needle-puncture-proof polyurethane coating arranged on the surface of the base fabric, wherein the thickness of the needle-puncture-proof polyurethane coating is 120-180 microns, and the needle-puncture-proof polyurethane coating is obtained by coating a polyurethane coating on the surface of the base fabric and curing the coating. The material of the base fabric is at least one of a chemical fiber material, a natural fiber material, and a mineral fiber material. The friction force is effectively increased by the needle-puncture-proof polyurethane coating, or by a polyurethane coating formed by adding glass fiber, quartz, and silicon carbide microparticle-type materials, thereby improving the needle-puncture-proof performance of the needle-puncture-proof fabric.
2. The polyurethane needle-proof fabric according to claim 1, characterized in that: The polyurethane coating comprises the following raw materials by weight: 85-90 parts of modified polyurethane emulsion, 20-25 parts of modified graphene oxide dispersion, 8-10 parts of modified whisker blended carbon fiber, and 5-7 parts of modified nano titanium dioxide.
3. The polyurethane needle-proof fabric according to claim 2, characterized in that: The preparation method of the modified nano titanium dioxide is as follows: 300 parts of nano titanium dioxide with a particle size of 20 nanometers, 7 parts of concentrated sulfuric acid with a mass concentration of 98%, 75 parts of xylene and 15 parts of 1,6-dipic acid are added into a three-necked flask with a stirring device and a thermometer according to the mass parts, the temperature is raised to 132° C., the temperature is kept until the acid value is less than 0.1 mgKOH / g, triethylamine is added to neutralize to a pH of 7.5, and the solvent is removed by negative pressure distillation to obtain the modified nano titanium dioxide.
4. The polyurethane needle-proof fabric according to claim 2, characterized in that: The method for preparing the modified whisker blended carbon fiber comprises the following steps: S41, according to the mass fraction, 100 parts of aluminum borate whiskers with a diameter of 1-5 μm and an aspect ratio of 10-15 are sent to 300 parts of concentrated sulfuric acid with a mass concentration of 95% for treatment for 40-60 minutes, and then washed with boiling water for 3 times and dried to obtain hydroxylated aluminum borate whiskers; S42. Add 100 parts of hydroxylated aluminum borate whiskers, 50 parts of carbon fibers with a diameter of 10-15 μm and an aspect ratio of 10-15, and 6 parts of silane coupling agents to 12 parts of an ethanol solution of sodium dithiopropane sulfonate with a mass concentration of 15%, stir thoroughly, and obtain modified whisker-blended carbon fibers.
5. The polyurethane needle-proof fabric according to claim 4, characterized in that: The silane coupling agent is composed of isopropyl trioleyl titanate, γ-aminopropyl triethoxysilane and tri(dodecylbenzenesulfonyl) isopropyl titanate in a mass ratio of 3:4:
3.
6. The polyurethane needle-proof fabric according to claim 2, characterized in that: The method for preparing the modified graphene oxide dispersion comprises the following steps: S61. According to the mass fraction, 10 parts of graphene oxide are added to 50 parts of N,N-dimethylformamide aqueous solution with a mass concentration of 5%, and stirred evenly. 0.3 parts of thionyl chloride are added at 0-4°C. After the addition is completed, the reaction is carried out for 3 hours, and the temperature is raised to 50°C. During the process, condensation and reflux are carried out and tail gas absorption is carried out at the same time. After the reaction is carried out for 6-8 hours, an appropriate amount of deionized water is slowly added until no gas is generated in the system, and then suction filtration and washing are carried out to obtain modified graphene oxide; S62. Re-disperse 10 parts of modified graphene oxide in 100 parts of water, disperse under high-speed stirring for 40 minutes, and then shear emulsify and homogenize for 4 hours to obtain a uniform dispersion, then add sodium 2-[(2-aminoethyl)amino]ethanesulfonate, react at 60°C for 8 hours to obtain a modified graphene oxide dispersion.
7. The polyurethane needle-proof fabric according to claim 6, characterized in that: The mass ratio of the modified graphene oxide to the sodium 2-[(2-aminoethyl)amino]ethanesulfonate is 1:3-4.
8. The polyurethane needle-proof fabric according to claim 2, characterized in that: The preparation method of the modified polyurethane emulsion comprises the following steps: S81. Mix 71 parts of di-terminal hydroxybutyl polydimethylsilane, 114 parts of butyl acrylate, 61 parts of styrene, 89 parts of polycaprolactone, 33 parts of isophorone diisocyanate, 3 parts of hydroxyethyl methacrylate, 1.8 parts of azobisisobutyronitrile, 0.5 parts of dibutyltin dilaurate and 10.5 parts of n-hexadecane in parts by mass to obtain a mixture; S82. Add the mixture into 300 parts of an aqueous emulsifier solution with a mass concentration of 5%, and then pre-emulsify at 2000r / min to obtain a crude emulsion. Use a cell crusher to perform ultrasonic treatment for 30 minutes in an ice-water bath to obtain a monomer fine emulsion. Finally, stir the obtained monomer fine emulsion in a nitrogen atmosphere for 1 hour, transfer it to a three-necked flask, maintain the temperature at 70°C, and carry out a fine emulsion polymerization reaction in a nitrogen environment for 6 hours to obtain a modified polyurethane emulsion.
9. The polyurethane needle-proof fabric according to claim 8, characterized in that: The emulsifier is 1-allyloxy-3-4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate.
10. A method for preparing a polyurethane needle-proof fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101, uniformly stirring the modified polyurethane emulsion, the modified graphene oxide dispersion, the modified whisker-blended carbon fiber and the modified nano-titanium dioxide according to their weight fractions to obtain a polyurethane coating; S102, applying the polyurethane coating on the surface of the base fabric, ensuring that the polyurethane coating can completely cover the base fabric and penetrate into the fibers thereof; S103, pressing the base fabric coated with the polyurethane coating so that the gaps in the base fabric are completely filled with the polyurethane coating, and then drying at 80-85° C. for 30-40 minutes to obtain the polyurethane anti-needle puncture fabric.
